1993
DOI: 10.1161/01.hyp.22.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific effects of an insulin secretagogue in stroke-prone hypertensive rats.

Abstract: Glyburide, an insulin secretagogue and an insulin-sensitizing agent, lowers blood pressure in normal male and female dogs when administered acutely. Because insulin resistance may contribute to spontaneous hypertension in rats, we sought to determine if long-term administration of glyburide (5 mg/kg per day by diet, age 5 weeks to 5 months) would lower blood pressure in male and female stroke-prone spontaneously hypertensive rats. Arterial (aortic) rings from these rats were incubated with insulin in vitro (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…By blocking the NO pathway, minor contractions were detected, suggesting the local involvement of the prostanoid system (11,36) and muscarinic Ach receptors (37) in addition to the NO pathway. It has been shown that insulin-dependent relaxation of the large vessels (aorta) and gracilis arterioles are predominantly mediated by NO and endothelium-derived hyperpolarizing factor/potassium channels, respectively (38).…”
Section: Figurementioning
confidence: 99%
“…By blocking the NO pathway, minor contractions were detected, suggesting the local involvement of the prostanoid system (11,36) and muscarinic Ach receptors (37) in addition to the NO pathway. It has been shown that insulin-dependent relaxation of the large vessels (aorta) and gracilis arterioles are predominantly mediated by NO and endothelium-derived hyperpolarizing factor/potassium channels, respectively (38).…”
Section: Figurementioning
confidence: 99%
“…6 Cells were maintained in growth medium (Dulbecco's modified Eagle medium supplemented with 9% fetal bovine serum, 0.2% Tylosin, 100 U/tnL penicillin, and 0.1 mg/mL streptomycin) and placed in a 37°C water-jacketed incubator under 5% CO 2 4. Blood clots, fat, and connective tissue were removed.…”
Section: Effects Of Pioglitazone On Calcium Channels In Vascular Smoomentioning
confidence: 99%
“…17 Conversely, glyburide, a sulfonylurea antidiabetic agent, increases both plasma insulin concentrations and blood pressure in female (but not in male) stroke-prone SHR. 18 The purpose of the present study was to define the relation between changes in insulin sensitivity and attenuation of hypertension. We have extended our studies in the DS rat to include the 1K1C Sprague-Dawley rat.…”
mentioning
confidence: 99%